Glycemic index and glycemic load of brief sugary sweets: randomized controlled trials of eight Thai desserts - Namjud, Nuttaphat; Senaprom, Sayamon; Ondee, Thunnicha; Bumrungpert, Akkarach; Heath, Julia; Pongpirul, Krit (Frontiers in Nutrition, 2024)
Thai desserts, celebrated for their exquisite sweetness, are widely enjoyed for personal indulgence and as cherished souvenirs. However, their high sugar content raises concerns regarding health impacts. This study aimed to quantify the Glycemic Index (GI) and Glycemic Load (GL) in healthy volunteers following consumption of various Thai desserts characterized by differing sugar levels. Out of ten renowned desserts from across Thailand, identified by the Tourism Authority of Thailand.Eight were selected based on the absence of preservatives, and microbial or chemical contaminations.Each participant consumed a 50g serving of available carbohydrate (50avCHO) from these desserts.Ninety-six healthy volunteers, with a mean age of 31.85.7 years, a mean body weight of 57.27.3 kg, and 63.5% female, were randomized into eight groups, with each group comprising twelve participants. Blood samples were collected pre-and post-consumption to assess GI and GL values following established protocols.The findings revealed that Phetchaburi's Custard Cake exhibited the lowest GI and GL values (53.4 & 26.7, respectively), with progressively higher values observed in Saraburi's Curry Puff (61.8 & 30.9),